New Zealand Pew Survey ‘Spring 2021’ COVID-Related Results - Crothers, C (School of Social Sciences, Auckland University of Technology, 2021)
NZ results relating to Covid of a ‘Spring’ Pew Research center survey are presented. NZers tend to be strong supporters of NZ’s handling of the Covid outbreak.
Keywords: New Zealand; Pew; Survey; Covid